Pathogenic and molecular characterization of Pythium species inducing root rot symptoms of common bean in Rwanda - Nzungize, J; Gepts, Paul L.; Buruchara, Robin Arani; Buah, Saaka S.J.; Ragama, P.E.; Busogoro, J.P.; Baudoin, Jean-Pierre (2011)
Pythium root rot constitutes a highly damaging constraint on the common bean, Phaseolus vulgaris L., grown in several areas of Eastern and Central Africa. Here, this food legume is cultivated intensively under poor conditions of crop rotation due to the exiguity of the land in the region. Yield losses of up to 70% in traditional local bean cultivars have been reported in Kenya and Rwanda. In this study, a detailed analysis of the biology and diversity of the Pythium genus was carried out in order to understand the mechanisms leading to the development of the disease. Various control methods for reducing the damage provoked by this disease were analyzed.